Livestock grazing in protected areas and its effects on large mammals in the Hyrcanian forest, Iran. (January 2018) - Soofi, Mahmood; Ghoddousi, Arash; Zeppenfeld, Thorsten; Shokri, Shirko; Soufi, Mobin; Jafari, Abbas; Ahmadpour, Mohsen; Qashqaei, Ali T.; Egli, Lukas; Ghadirian, Taher; Chahartaghi, Niloufar Raeesi; Zehzad, Bahram; et al.
Abstract: Protected areas are the most important tool to safeguard large mammals from overexploitation, but their effectiveness is insufficiently studied in temperate ecosystems. The Hyrcanian forest is one of the oldest and most threatened temperate forests globally. Anthropogenic activities are widespread and negatively affect wildlife species in the Hyrcanian forest. We conducted surveys in 22% of the Hyrcanian forest by walking 1204 km in 93 16-km 2 cells distributed randomly in 18 protected and non-protected study sites. We used Bayesian occupancy modeling to measure the effects of livestock grazing, logging and poaching on distribution of six large mammal species. Our results explicitly show that grazing had negative and significant impact on the occupancy of very patchily distributed Persian leopard ( β = − 1.65, Credibility Interval − 2.85 to − 0.65), Caspian red deer ( β = − 1.36, CI − 2.34 to − 0.45) and roe deer ( β = − 1.61, CI − 2.96 to − 0.58) while logging did so for red deer ( β = − 0.82, CI − 1.69 to − 0.03). Poaching could not be determined due to low detectability of poaching signs. Grazing intensity was high in protected areas (IUCN category V), no-hunting and non-protected areas and much lower in national parks (II) and wildlife refuges (IV). Representing 66% of total reserves in the Hyrcanian forest, category V protected areas urgently require priority actions in assessment of grazing capacities, allocation and enforcement of grazing quotas, and better coordination between governmental conservation and natural resource management organizations to avoid further depletion of the large mammal community in the Hyrcanian forest. Highlights: The urgent need for regulating the livestock grazing in the Hyrcanian forest Fragmented distribution of endangered species reflects inefficiency of law enforcement. Category V reserves urgently require actions in assessing of grazing capacities.